Importance of the vacuum in rapid tooling of polymeric-based moulds - P. V. Vasconcelos (2004)
Metallic powders are typically mixed with epoxy and polyurethane resin systems to improve the moulds thermal conductivity. The critical problem to produce these mixtures for Rapid Tooling applications is the difficulty of eliminating the entrapped air, introduced during the processing due to the high viscosity of the mixture, especially in the presence of high aluminium concentrations. When air bubbles are retained in the resin/model interface, superficial defects are generated which render inoperative the Rapid Tooling moulds, and consequently the advantages of these new technologies. In this work, a specific methodology is presented to reduce the porosity level, not only in these typical mixtures, but also in hybrid ones, manufactured with aluminium particles and milled fibres, which have a even worse tendency to produce pores in the composite interface.